Process evaluation of specialist nurse implementation of a soft opt-out organ donation system in Wales - Jane Noyes; Leah Mclaughlin; Karen Morgan; Abigail Roberts; Bethan Moss; Michael Stephens; Phillip Walton (BMC, 2019)
Abstract Background Wales introduced a soft opt-out organ donation system on 1st December 2015 with the aim of improving consent rates. In the first 18 months consent rates improved but the difference could not solely be attributed to the soft opt-out system when compared with similar improvements in consent rates in other UK nations. Methods We conducted an 18 month post-intervention qualitative process evaluation involving 88 family members of 60/211 potential organ donor cases, and 19 professionals. Views and experiences of Specialist Nurses in Organ Donation who implemented the new system and family members who were involved in decision making were collected to see how their respective behaviours impacted on implementation. Data collection included interviews, focus groups and qualitative questionnaire data. Results Implementation was considered a success by Specialist Nurses in Organ Donation. The bespoke retraining programme and responsive approach to addressing initial implementation issues were identified as examples of best practice. Specialist Nurses in Organ Donation were valued by family members. Six implementation issues had an impact on consent rates - the media campaign had gaps, the system was more complex, challenges in changing professional behaviours, inability to obtain the required standard of evidence from family members to overturn a donation decision, increased complexity of consent processes, and additional health systems issues. Conclusion This is the first comprehensive process evaluation of implementing a soft opt-out system of organ donation. Specific elements of good implementation practice (such as investment in the retraining programme and the responsiveness of Specialist Nurses in Organ Donation and managers to feedback) were identified. The key message is that despite retraining, nursing practice did not radically change overnight to accommodate the new soft opt-out system. Policy makers and health service managers should not assume that nurses simply need more time to implement the soft-out as intended. Additional responsive modification of processes, ongoing training and support is required to help with implementation as originally intended. Scotland, England and the Netherlands are introducing soft opt-out systems. There is an opportunity to learn from initial implementation in Wales, by acknowledging gaps, good practice and opportunities to further improve processes and nursing practices.